Numerical study of an anisotropically supported rotor with parametric excitation - Lee, Chih Feng; Tan, Yee Wei; Krodkiewski, Janusz M. , Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/